Minimum Requirement to Improve Quality before Discharging from Hybrid Red Tilapia Intensive Cage-Culture in Earthen Ponds to the Environment: 10.32526/ennrj/20/202100208 - Taparhudee, Wara; Is-haak, Jesada; Jongjaraunsuk, Roongparit (Environment and Natural Resources Journal, 2022)
This study determined a practical method to reduce environmental pollution by wastewater from fish ponds. Water quality in three hybrid red tilapia ponds (0.24 ha) was examined before and during harvest at five water depths of 10, 20, 50, 100, and 150 cm, as well as at the water surface and pond bottom. All water samples were analyzed for BOD, TN, TP, TAN, TS, TSS, and SS, with results compared with the Thailand control standard for freshwater aquaculture effluent. All quality parameters of the seven water samples showed statistical significance (p<0.05) that increased with water depth. Degradation was highest in the bottom 50 cm of the fish pond. Limiting drainage to a depth of 50 cm was achieved by tilting the drainage pipe, and the resulting effluent met all water quality parameter standards. At a water depth of 50 cm, the remaining water was drained using a water pump, and all water quality parameters failed to meet the required standards. When this water was allowed to settle for 24 h, BOD, TN, TP, TAN, and TSS reduced to 21.06%, 2.42%, 11.68%, 5.47%, and 43.36% of full pond values, respectively. Results suggested sedimentation as a practical technique requiring a smaller pond area to reduce environmental pollution.